Towards an architecture for service deployment in contributory communities. (6th August 2009) - Lazaro, Daniel; Marques, Joan Manuel; Jorba, Josep
This paper proposes an architecture and a set of mechanisms for deploying services in a decentralised contributory system, i.e. a system that runs using only the resources contributed to the community by its members. We present the layers that form our architecture and show the existing technologies that can be used to implement some of them. We show how our mechanisms make use of these layers and how they interact to allow the deployment of services in a decentralised way. The resources contributed by the members of the community are used to host the services deployed in it, while achieving desirable characteristics such as scalability, decentralisation, ability to deal with heterogeneity, fault tolerance, load-balancing and self-properties.